The thank you economy - Vaynerchuk, Gary, ....- (New York : Harper Collins, 2011)
If this were 1923, this book would have been called "Why Radio Is Going to Change the Game" . . . If it were 1995, it would be "Why Amazon Is Going to Take Over the Retailing World" . . . The Thank You Economy is about something big, something greater than any single revolutionary platform. It isn't some abstract concept or wacky business strategy-it's real, and every one of us is doing business in it every day, whether we choose to recognize it or not. It's the way we communicate, the way we buy and sell, the way businesses and consumers interact online and offline. The Internet, where The Thank You Economy was born, has given consumers back their voice, and the tremendous power of their opinions via social media means that companies and brands have to compete on a whole different level than they used to. Gone are the days when a blizzard of marketing dollars could be used to overwhelm the airwaves, shut out the competition, and grab customer awareness. Now customers' demands for authenticity
Originality, creativity, honesty, and good intent have made it necessary for companies and brands to revert to a level of customer service rarely seen since our great-grandparents' day, when business owners often knew their customers personally, and gave them individual attention. Here renowned entrepreneur Gary Vaynerchuk reveals how companies big and small can scale that kind of personal, one-on-one attention to their entire customer base, no matter how large, using the same social media platforms that carry consumer word of mouth. The Thank You Economy offers compelling, data-driven evidence that we have entered into an entirely new business era, one in which the companies that see the biggest returns won't be the ones that can throw the most money at an advertising campaign, but will be those that can prove they care about their customers more than anyone else. The businesses and brands that harness the word-of-mouth power from social media, those that can shift their culture to be more customer-aware
And fan-friendly, will pull away from the pack and profit in today's markets. Filled with Vaynerchuk's irrepressible candor and wit, as well as real-world examples of companies that are profiting by putting Thank You Economy principles into practice, The Thank You Economy reveals how businesses can harness all the changes and challenges inherent in social media and turn them into tremendous opportunities for profit and growth.
Keywords: Economie : innovatie; Economie; Marketing